PERBEDAAN PENGETAHUAN GIZI, SIKAP DAN PERILAKU TENTANG VISUAL GIZI SEIMBANG ANTARA DUA GENERASI DI GEREJA GSKI REHOBOT KEBON JERUK JAKARTA - Parapat, Ruth Gracia Dau Vanes; Melani, Vitria; Wahyuni, Yulia; Nuzrina, Rachmanida; Sitoayu, Laras (Journal of Nutrition College, 2021)
Background: Generation Y (Millennial) and generation Z (IGeneration) are proven to be the two generations that dominate the use of information communication technology today. Living in a rapidly developing technology era and abundant information should make them have nutritional knowledge, attitudes and behavior towards a good visual balanced nutrition. However, Riskesdas 2018 shows an increase in the prevalence of obesity in adults by 21.8%. This high prevalence is said to be an indicator of low knowledge about balanced nutrition even though the two generations live in an era of abundant information.Objectives: Analyzing differences in nutritional knowledge, attitudes and behavior regarding visual balanced nutrition between generation Y and generation Z.Methods: This research is an observational analytic study with cross sectional design. Selection of research subjects with total sampling. A sample of 40 respondents was obtained from generation Y and 40 respondents from generation Z. Using the independent t-test statistical test to determine differences in nutritional knowledge, attitudes and behaviors regarding balanced nutrition visuals (balanced nutrition cone and my plate) in generation Y and generation Z.Results: There are differences in nutritional knowledge in generation Y and generation Z (p = 0.0001), there are differences in attitudes about visual balanced nutrition in generation and generation Z (p = 0.0001), and there are differences in nutritional behavior towards visual balanced nutrition of generation Y and generation Z (p = 0.029). From the above values, it can be said that the value of sampling bias on nutritional knowledge and attitudes is smaller than behavior.Conclusion: The three results show that there are differences in nutritional knowledge, attitudes and behavior between these two generations.